Direct variation:-
y = kx where k is a constant
y=12 when x=6 so we have:-
12 = k*6
k = 12/6 = 2
so our equation of variation is y = 2x Answer
Answer:
47/12, or 3 11/12
Step-by-step explanation:
9 1/2 - 5 7/12 > convert to improper fractions
19/2 - 67/12
make same denominator (12)
19/2 * 6 = 114/12
114/12 - 67/12 = 47/12
<h3>
Answer: 1/4 mile</h3>
Explanation:
A square has all four sides the same length. So the length and width are the same.
We can see that (length)*(width) = (1/4)*(1/4) = 1/16 square miles.
If you wanted, you could solve for W in (1/4)*W = 1/16 and you should get W = 1/4.
Note: In option A, it should be "+" instead of "(".
Given:
The expression is
![-2x(x+y-3)+3(-x+4y)+y(3x+5y-3)](https://tex.z-dn.net/?f=-2x%28x%2By-3%29%2B3%28-x%2B4y%29%2By%283x%2B5y-3%29)
To find:
The equivalent expression.
Solution:
We have,
![-2x(x+y-3)+3(-x+4y)+y(3x+5y-3)](https://tex.z-dn.net/?f=-2x%28x%2By-3%29%2B3%28-x%2B4y%29%2By%283x%2B5y-3%29)
Using distributive property, we get
![=-2x(x)-2x(y)-2x(-3)+3(-x)+3(4y)+y(3x)+y(5y)+y(-3)](https://tex.z-dn.net/?f=%3D-2x%28x%29-2x%28y%29-2x%28-3%29%2B3%28-x%29%2B3%284y%29%2By%283x%29%2By%285y%29%2By%28-3%29)
![=-2x^2-2xy+6x-3x+12y+3xy+5y^2-3y](https://tex.z-dn.net/?f=%3D-2x%5E2-2xy%2B6x-3x%2B12y%2B3xy%2B5y%5E2-3y)
On combining like terms, we get
![=-2x^2+5y^2+(-2xy+3xy)+(6x-3x)+(12y-3y)](https://tex.z-dn.net/?f=%3D-2x%5E2%2B5y%5E2%2B%28-2xy%2B3xy%29%2B%286x-3x%29%2B%2812y-3y%29)
![=-2x^2+5y^2+xy+3x+9y](https://tex.z-dn.net/?f=%3D-2x%5E2%2B5y%5E2%2Bxy%2B3x%2B9y)
The expression
is equivalent to the given expression.
Therefore, the correct option is A.
Yes since the four sides are always parallel in a square <span />